Dialogue and difference in a teacher education program : a 16-year sociocultural study of a professional development school - Johnston-Parsons, Marilyn (Emerald Publishing Limited : Information Age Publishing, 2012)
This book is a longitudinal study of a 10-year experimental teacher education program. Follow-up studies and writing continued for 6 years after the program closed. This case study describes a search for effective and socially just practices within a long-term reform initiative intended to prepare teachers for urban schools. The program was run through a Professional Development School--a collaboration between a university program and a diverse group of practicing teachers; and the book was written collaboratively by many of the participants--faculty, mentor teachers, doctoral students, and teacher candidates/graduates. There are few longitudinal studies of teacher education programs, especially ones that focus on what was learned and told by those who did the learning.The narratives here are rich, diverse, and multivocal. They capture the complexity of a reform initiative conducted within a democratic context. It's difficult, messy and as varied as is democracy itself. The program was framed by a sociocultural perspective and the focus was on learning through difference. Dialogue across difference, which is more than just talk, was both the method for doing research and the means for learning.The program described here began in the ferment of teacher education reform in the early 1990s, responding to the critics of the mid-1980s; and this account of it is finished at a time when teacher education is again under attack from a different direction. Criticized earlier for being too progressive, teacher education is now seen as too conservative. The longitudinal results of this program show high retention rates and ground the argument that quality teacher preparation programs for teaching in urban schools may well be cost effective, as well as provide increased student learning. This is counter to the current move to shorten teacher preparation programs, at a time of low teacher retention in our under resourced urban schools. The book does not advocate a model for teacher education, but it aims to provide principles for practice that include school/university collaboration, democratic dialogue across differences, and inquiry as a way to guide reform.
Keywords: Teachers -- In-service training -- United States -- Longitudinal studies.; Teacher participation in curriculum planning -- United States -- Longitudinal studies.; Educational change -- United States -- Longitudinal studies.; elektronické knihy; Longitudinal studies.; Education -- Teacher Training & Certification.; Teacher training.; electronic books